Entrepreneurship development among RISDA farmers in Malaysia / Muhammad Firos Mustaffa - Muhammad Firos, Mustaffa (2021)
Rubber farmers in Malaysia have been saddled with poverty, and mostly hard core. To overcome poverty, the government has supported farmers to engage in small businesses by providing training and grants, but only a small number of participants have succeeded. The study intends are to identify factors that influence the success or failure of small businesses in the context of RISDA farmers. A primary motivation for undertaking the study arises from the desire to understand why this programme had a high failure rather than a success rate, despite the fact that many resources were being given to these farmers to objectively raise their income and improve their well-being. This study fills the gaps in knowing the farmer's ability to engage in entrepreneurship by considering other dimensions such as internal and external factors. A quantitative approach using a questionnaire survey of 398 RISDA farmers who were enlisted as active for two years in small businesses was employed in this study. The study finds a significant relationship between support services, opportunities, self-efficacy, attitudes, as well as demographic factors and success or failure in small businesses. Among the main causes for their failure are a lack of knowledge and skills in small business, short of family support and inadequate training. Those who succeed in small businesses are found to have higher educational attainment, are middle-aged, and have the support of their family members. The study also ranked the important factors that influence small business success. The findings of the study may be used to enhance policy and programme design in order to increase the success rate of farmers in small businesses. The participants should be assessed on their business readiness before accepting them into the entrepreneurship development programme. Small business programmes should only target those with at least secondary schooling, while the authorities need to improve their monitoring, support services, and appropriate training of the recipients to ensure better success of the programmes. The study concludes that getting farmers out of poverty using entrepreneurial approach programs needs not only focus on financial support, but also other factors mentioned above.